Metas de logro, clima de apoyo a la autonomía, estrategias metacognitivas de aprendizaje y desorganización en estudiantes de psicología de una universidad privada de Lima Metropolitana - Diez Canseco Gómez, Carolina Mariana (2016)
The aim of this research was to relate achievement goals with autonomy support, metacognitive learning strategies and disorganization, in a sample of 175 psychology students at a private university in Lima. The sampling method used, was not probabilistic accidental type. Psycometric results show evidence of reliability and validity related to the internal structure of the instruments. Regarding the Achievement Goals Questionnaire (AGQ), the factor analysis’s results disagreed with the theory, since it evidenced a two variable structure, instead of three. Moreover, the student’s approach to learning goals is associated with autonomy support and metacognitive strategies; whereas it relates negatively with disorganization.